Advanced Technologies in Rehabilitation - Wiederhold, Brenda K. (IOS Press, 2013)
Cybertherapy – the provision of healthcare services using advanced technologies – can help improve the lives of many of us, both patients and health professionals, while tackling the challenges of healthcare system. It is recognized that integrating these new types of services in healthcare systems is a challenging task. The aim of this book is to support and encourage all the interested countries in this endeavor, by identifying and helping to address the main barriers hindering the wider use of cybertherapy and by providing evidence to build trust and acceptance. The structure of the book is divided in four main sections: 1) Critical Reviews: summarizes and evaluates emerging cybertherapy topics, including Interreality, CyberAddiction and Telemedicine; 2) Evaluation Studies: are generally undertaken to solve some specific practical problems and yield decisions about the value of cybertherapy interventions; 3) Original Research: presents research studies addressing new cybertherapy methods or approaches; 4) Clinical Observations: includes case studies or research protocols with a long-term potential.